Realidad virtual como buena práctica para trabajo en equipo con estudiantes de ingeniería (2015)
Virtual reality is an alternative for student's motivation, allowing them actions like flying or observing the environment from different perspectives in a controlled way. Multiuser interaction in virtual reality leads to collaborative virtual environments that promote the development of social skills in teamwork, in particular with members in different geographic locations. In these contexts there are different virtual reality application proposals transporting students to environments where they make team decisions for achieving intended goals. However, such proposals do not emphasize the importance of identifying the strengths of each team member for the improvement in the team performance. This paper presents a virtual reality-based videogame incorporating gamification principles for promoting and improving teamwork in engineering students.